Early antibody responses to rabies post-exposure vaccine regimens. - Suntharasamai, P; Warrell, M; Warrell, D; Chanthavanich, P; Looareesuwan, S; Supapochana, A; Phanuphak, P; Jittapalapongsa, S; Yager, P; Baer, G (1987)
The aim of post-exposure rabies vaccine treatment is to induce immunity, measured as neutralizing antibody, as fast as possible. This is especially important in the tropical rabies-endemic areas where simultaneous passive prophylaxis with hyperimmune serum is not practicable in the majority of cases. We compared the rate of production of antibody during the first two weeks, by six vaccine regimens in 118 subjects using two tissue culture vaccines, human diploid cell strain vaccine (HDCSV) and purified Vero cell rabies vaccine (PVRV). No antibody was detected on day 5. On day 7, the highest seroconversion rate was seen in subjects given HDCSV intramuscularly at two sites on days 0 and 3 (7 of 15), but this was not significantly different from the group with the lowest rate: the conventional single-site intramuscular regimen. All subjects had antibody by day 14, at which time the highest geometric mean titer was in the group vaccinated with 0.25 ml doses of diploid cell vaccine given subcutaneously at eight sites. This regimen, together with the standard single-site diploid cell vaccine and an eight-site intradermal regimen of the same product gave significantly higher titers than the two-site intramuscular regimens of either product. No single immunization schedule emerges as best, so the speed of antibody response, economy, and the skill needed for intradermal injection should be considered when deciding on the optimum regimen for use in a particular geographic area.